Unveiling Differentiation Characteristics of Vegetation Restoration Potential for Browning Areas in China’s Hilly and Gully Region - Juan He; Wei Zhou; Mingjie Qian; Enmao Zha; An Cao; Xueyi Shi (Land)
Vegetation greening resulting from ecological engineering efforts has statistically contributed to environmental improvement, through enhancing ecosystem effectiveness remains a challenge. Nevertheless, there has been a notable lack of research dedicated to enhancing vegetation resilience and restoration potential by mitigating vegetation browning in watersheds within arid and semi-arid regions. This study fills that gap by identifying the spatial heterogeneity in ecological resilience using statistical analyses and an exponential decay approach. It then evaluates the potential for ecological restoration by optimizing ecosystem structures in browning areas based on resilience and reference state. The key findings included the following: (1) With a narrower interquartile range, kNDVI values from 2015 to 2023 demonstrated notable increases as compared to 2000–2014. The northern and eastern sub-watersheds showed greater vegetation restoration, but the southern regions showed less resilience. (2) Vegetation resilience in the majority of sub-watersheds was concentrated at moderate levels, and the number of grids with strong positive tendencies decreased, according to the analysis of grid trends. (3) Fifteen reference states were established for browning areas based on the current natural conditions. The larger restoration potential ratio showed notable differences in sub-watershed restoration, indicating opportunities for improvement. Extreme vegetation degradation demonstrated little potential for restoration in resource-poor areas. This study provides valuable insights into integrating resilience and restoration potential into ecological restoration practices, advancing the application of ecological engineering strategies.